A Model to Predict Psychological- and Health-Related Adjustment in Men with Prostate Cancer: The Role of Post Traumatic Growth, Physical Post Traumatic Growth, Resilience and Mindfulness - Walsh, Deirdre M. J.; Morrison, Todd G.; Conway, Ronan J.; Rogers, Eamonn; Sullivan, Francis J.; Groarke, AnnMarie (Frontiers in Psychology, 2018)
Background: Post traumatic growth (PTG) can be defined as positive change following a traumatic event. The current conceptualization of PTG encompasses five main dimensions, however, there is no dimension which accounts for the distinct effect of a physical trauma on PTG. The purpose of the present research was to test the role of PTG, physical post traumatic growth (PPTG), resilience and mindfulness in predicting psychological and health related adjustment. Method: Ethical approval was obtained from relevant institutional ethics committees. Participants (N = 241), who were at least 1 year post prostate cancer treatment, were invited to complete a battery of questionnaires either through an online survey or a paper and pencil package received in the post The sample ranged in age from 44 to 88 years (M = 64.02, SD = 7.76). Data were analysis using confirmatory factor analysis and structural equation modeling. Results: The physical post traumatic growth inventory (P-PTGI) was used to evaluate the role of PPTG in predicting adjustment using structural equation modeling. P-PTGI predicted lower distress and improvement of quality of life, whereas conversely, the traditional PTG measure was linked with poor adjustment. The relationship between resilience and adjustment was found to be mediated by P-PTGI. Conclusion: Findings suggest the central role of PTG in the prostate cancer survivorship experience is enhanced by the inclusion of PPTG. Adjusting to a physical trauma such as illness (internal transgressor) is unlike a trauma with an external transgressor as the physical trauma creates an entirely different framework for adjustment. The current study demonstrates the impact of PPTG on adjustment. This significantly adds to the theory of the development of PTG by highlighting the interplay of resilience with PTG, PPTG, and adjustment.